Separação de misturas azeotropicas da gasolina utilizando liquidos ionicos proticos (LIP's). - Pinheiro, Regiane Silva (2017)
In this work different protic ionic liquids (PIL’s) were produced by varying the base and acid chain used for synthesis, in an attempt to produce a more selective LIP for the association with the alcohols of the azeotropic mixture, alkane + alcohol. The PIL’s were produced in the laboratory by slow neutralization reaction, then dried, analyzed and stocked. The study of binary systems between ionic liquid and water; and ionic liquid + ethanol served to study the polarities of the solvents. The binary mixtures were weighed in tubes glass and they were mixture in a vortex, then it was measured density, viscosity and velocity of sound and the properties excess volume and excess Gibbs energy were calculated. It has been found that the density exhibits a linear behavior with temperature and viscosity an exponential behavior. In study of ternary mixtures, titration and densimetry techniques were used for the construction of the binodal curve and quantification of the raffinate and extract phases after the process of separation of the mixtures. The distribution coefficients and the selectivity parameter were calculated with the objective of studying the preferred phase for the migration of the solute and the potential extractor of the solvents. The solutes studied, methanol and ethanol, migrated to the solvent-rich phase (2-HEAF and 2-HEAA) and the selectivity results were in addition to the unit, indicating an excellent extractor character of the ionic liquids studied. The NRTL thermodynamic model presented satisfactory results for all correlations, the mean calculated error was less than 2%.